RETRACTED : The Influence of Compensation, Leadership Style and Organizational Culture on The Performance of Employees of PT. Astra Honda Motor Plant Sunter in 2018 - Mohamad Ilham Eska Kurniawan; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science, 2024)
This research is useful to analyze the influence of compensation, leadership style and organizational culture on the performance of PT Astra Honda Motor Plant Sunter, Jakarta. PT Astra Honda Motor Plant Sunter has a worsening performance from year to year, performance data can be seen from the average performance appraisal results. The results of this study used primary data in the form of questionnaires to 100 employees of PT Astra Honda Motor Plant Sunter as respondents, using multiple linear regression method. The conclusion obtained shows the three independent variables studied separately have a positive and significant effect on employee performance PT Astra Honda Motor plant Sunter. Each research variable, the results in some of the indicator statements declare neutral this research. PT Astra Honda Motor Sunter should be able to improve some of the indicators of compensation, leadership style and organizational culture to a better level or with a statement agree, and even strongly agree that improve the performance of PT Astra Honda Motor plant Sunter employees.